VEJA o discurso psiquiátrico - Chads, Bruno Holmes (2010)
This work had as objective to analyze certain news of Veja magazine and think the relationship between midia and scientific discourse, how the credibility of this one can be borrowed by the other with the intention of supporting some everyday s morals rules, that is, the common sense. Here is it s ideological characteristic. More precisely, it was the discourse of psychiatry, knowledge that pretentiously arrogates itself as a scientific knowledge, the one considered, because to it is made, constantly, reference to orientate the readers of the magazine in their personal impasses.